Five Easy Pieces: Reframing the Design of Office Systems - Greenbaum, Joan; Madsen, Kim Halskov (DAIMI Report Series, 1988)
Problems with the use of computer systems may often be traced back to the designers’ narrow view or understanding of office work. Neither office work nor design of office systems should be done strictly according to rules or procedures. Similar cases, examples and previous situations play just as important a role. In the spirit of this, we present, not a set of guidelines for design, but five pieces or exercises that stimulate seeing things in new ways. We use metaphors as a way to interpret computer system use. And by the dichotomous ideas of description versus interpretation, similarity and differences, planned action versus situated action, group discussion against indiuidual problem-solving, and authoritative knowledge against shared knoweldge, we hope to set in motion a dialectical reframing process.